EVALUASI PASCA HUNI TERHADAP PERFORMANSI FISIK RUANG INSTALASI GAWAT DARURAT - Sumantri, Triandari; Hariyono, Widodo; Iswanta, Iswanta (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2016)
Background: One of the assessment criteria for hospital services was health services provided by paramedics who were in the emergency room. This study aims was to describe from the emergency room users for the physical condition of emergency room during a post occupancy evaluation of emergency room PKU Muhammadiyah Yogyakarta Unit II Hospital. Method: This study was a descriptive observational approach. The population in this study was the internal and external users emergency room. The total sample was 56 respondents. Data analysis performed using triangulation to data processing and conclusions. Results: Physical performance showed emergency room location is easily accessible by the patient but on the other side is still not enough to accommodate some transportation at the same time. The lighting and moisture level were 328 lux and 58% respectively. However, the noise level and the room temperature were 55.8 dB and 27.8oC. According to the result of observation in 5 location, the result for safety category, security and comfort were good. Conclusion: Based on users perception views from safety category, security category and comfort needs to be improved. Location, lighting, humidity and temperature in emergency room were not fulfill the standard yet.